Compound anti-aging skin-firming polypeptide skin care product and preparation method thereof
Patent Information
- Application Number
- CN202411894662.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-02-21
AI Technical Summary
Among the existing anti-aging skin care products, the stability, transdermal absorption efficiency and long-term release ability of bioactive peptides are insufficient, resulting in a short time to act in the skin environment and cannot meet the long-term anti-aging needs.
Using acetyl octapeptide-3 nanoparticles and copper peptide nanolipid complexes, the preparation of glutamine-based nanoparticles and high-pressure homogenization of copper peptides is improved to improve the stability and transdermal absorption of active peptides. and prolong its action time through a sustained release mechanism.
It significantly improves the stability, transdermal absorption efficiency and long-term release performance of the active peptide, extends the anti-wrinkle effect, enhances collagen production and skin tightening effects, and meets the needs of long-term anti-aging skin care.
Smart Images

Figure CN119488454A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of skin care products, and in particular to a compound anti-aging and skin-tightening polypeptide skin care product and a preparation method thereof. Background Art
[0002] With the growing demand for skin care and anti-aging in modern society, the skin care industry has put forward higher requirements for the research and development of efficient anti-aging products. In practical applications, consumers not only pay attention to the short-term efficacy of skin care products, but also expect that they can significantly improve the skin condition and delay the aging process after long-term use. Especially in anti-aging skin care products, bioactive peptides have become the core functional ingredients that have attracted much attention because of their good anti-wrinkle, collagen production and skin barrier repair effects. However, in order to meet the needs of actual application scenarios, the efficacy of bioactive peptides needs to overcome a variety of limitations, including their stability during use, transdermal absorption efficiency and long-term sustained release ability. Especially in complex skin environments (such as pH, temperature, humidity and other variable conditions), active peptides need to remain efficient and stable, while being able to continuously act on the deep layers of the skin, thereby achieving a comprehensive effect of anti-wrinkle and firming. In addition, the ease of use, environmental adaptability and service life of skin care products are also important performance indicators. For example, anti-aging skin care products need to work effectively under different skin types and environmental conditions, while ensuring their safety in storage and use. Therefore, improving the stability, transdermal absorption efficiency and long-term sustained release performance of bioactive peptides can not only significantly enhance the anti-aging effect of the product, but also broaden its application range, promote technological progress in the anti-aging field, and further meet consumers' urgent demand for high-efficiency skin care products.
[0003] Although bioactive peptides have been widely studied in the field of skin care products due to their excellent anti-aging and skin tightening properties, the current technology still faces many deficiencies. For example, the Chinese patent with publication number CN107822973A discloses a polypeptide beauty skin care product containing active peptides, which improves the anti-wrinkle effect of active peptides by optimizing the formula, but it lacks the ability to be continuously released in the skin environment, resulting in a short action time of the active ingredients, which cannot meet the needs of long-term anti-aging. In addition, the patent with publication number CN108938453A discloses a technology in which a skin care product successively coats polypeptide proteins with sodium hyaluronate and silicone. Although it improves the transdermal absorption efficiency of active peptides to a certain extent, the stability of its encapsulation system is poor and is easily affected by storage conditions and skin environment, resulting in degradation and loss of function of active peptides. The main reason for the above-mentioned deficiencies is that the existing materials and technologies fail to take into account the three key properties of stability, long-term release and transdermal absorption of active peptides at the same time. On the one hand, the molecular structure of active peptides is relatively fragile and easily degraded by environmental factors (such as oxidation, light, high temperature, etc.); on the other hand, existing carrier materials such as liposomes and polymer systems still have great limitations in controlling the release rate of active peptides and enhancing skin penetration. Therefore, how to develop new carrier materials with high stability, high permeability and long-term release ability has become a key issue in solving the bottleneck of the application of bioactive peptides in anti-aging skin care products. Summary of the invention
[0004] (1) Technical solution In order to achieve the above object, the present invention provides the following technical solutions: A compound anti-aging and firming polypeptide skin care product comprises the following components in weight fractions: 2.0-5.0 parts of loaded acetyl octapeptide-3 nanoparticles, 1.0-2.0 parts of copper peptide nanolipid complexes, 1.0-3.0 parts of palmitoyl pentapeptide-4, 0.5-1.5 parts of sodium hyaluronate, 3.0-5.0 parts of glycerol, 2.0-4.0 parts of butylene glycol, 2.0-4.0 parts of squalane, 1.0-3.0 parts of caprylic / capric triglyceride, 1.5-3.0 parts of polysorbate-60, 0.2-0.4 parts of carbomer, 0.1-0.3 parts of xanthan gum, 0.2-0.3 parts of triethanolamine, and vitamin E. 0.5~1.0 parts, panthenol 0.5~1.0 parts, seaweed extract 0.5~1.0 parts, phenoxyethanol 0.6~0.8 parts, ethylhexylglycerin 0.5~1.0 parts, coenzyme Q10 0.5~1.0 parts, resveratrol 0.5~0.8 parts, ceramide 0.5~1.0 parts, cholesterol 0.2~0.5 parts, phospholipids 1.0~2.0 parts, disodium EDTA 0.1~0.3 parts, sodium ascorbyl phosphate 0.1~0.2 parts, propylene glycol 1.0~2.0 parts, deionized water 60.0~65.0 parts, citric acid-sodium citrate buffer 0.05~0.1 parts.
[0005] The acetyl octapeptide-3 loaded nanoparticles are composed of glutamine-based nanoparticles and acetyl octapeptide-3 loaded on the glutamine-based nanoparticles; The glutamine-based nanoparticles are prepared by copolymerization of hydroxyethyl methacrylate and N-methacryloyl-(L)-glutamic acid through emulsion polymerization. The N-methacryloyl-(L)-glutamic acid is obtained by chlorination reaction of L-glutamic acid-5-methyl ester and methacryloyl chloride; The copper-peptide-lipid nanocomposite liposome is prepared from copper peptide and nanoliposome by emulsification combined with high-pressure homogenization technology; The pH of the polypeptide skin care product is 4.5-5.5.
[0006] Furthermore, the preparation method of the acetyl octapeptide-3 loaded nanoparticles is as follows: by weight, 2.0-5.0 parts of glutamine-based nanoparticles and 0.01-0.03 parts of sodium chloride are added to 30-40 parts of 0.4 mg / mL acetyl octapeptide-3 solution, the mixture is placed in a beaker, the stirring rate is 30-40 rpm, the stirring time is 20-40 min, and the pH of the solution is adjusted to 3.4-6.0 with a citric acid buffer during the stirring process. After the stirring is completed, the obtained nanoparticle suspension is transferred to a centrifuge, centrifuged at a speed of 10000-12000 rpm for 20-25 min, the supernatant is discarded, and the nanoparticle precipitate is separated. The obtained precipitate is washed 3 times with deionized water, and the amount of each washing is twice the volume of the suspension. After the washing is completed, the washed nanoparticle suspension is frozen with liquid nitrogen and placed in a freeze dryer for 20-24 h to finally obtain acetyl octapeptide-3 loaded nanoparticles.
[0007] Further, the preparation method of the glutamine-based nanoparticles is as follows: in parts by weight, deionized water is used as a solvent, 270.0-280.0 parts of polyvinyl alcohol are dissolved in 20.0-30.0 parts of deionized water, the mixture is placed in a beaker, the stirring rate is set to 300-350 rpm, the stirring time is 30-40 min, until a uniform mixed solution is formed, then 0.50-0.65 parts of hydroxyethyl methacrylate, 0.80-1.1 parts of N-methacryloyl-(L)-glutamic acid and 0.29-0.31 parts of ethylene glycol dimethacrylate crosslinking agent are sequentially added to the above-mentioned mixed solution, the stirring rate is 300-350 rpm, and the stirring is continued for 20-30 minutes until a uniform reaction solution is formed, 18.0-20.0 parts of 50 wt.% potassium persulfate solution are slowly added dropwise to the above-mentioned reaction solution, and at the same time, the flow rate is 10.0-12.0 Nitrogen was purged at sccm for 240-360 s to remove oxygen from the solution. The mixed solution was heated to 60-70°C at a heating rate of 2°C / min and stirred at a stirring rate of 120-150 rpm for 240-300 min under the heating condition until the reaction was complete and an emulsion mixture was formed. After the reaction was completed, the mixture was naturally cooled to room temperature. The cooled emulsion was transferred to a centrifuge and centrifuged at a centrifugal rate of 11000-12000 rpm for 20-25 min. The precipitate was separated and the supernatant was discarded. The obtained precipitate was washed alternately with anhydrous ethanol and deionized water for 3-5 times, each time with an amount twice that of the precipitate, to remove unreacted monomers and impurities. After washing, the precipitate was placed in a vacuum drying oven and dried at room temperature for 16-20 h to finally obtain glutamine-based nanoparticles.
[0008] Furthermore, the preparation method of N-methacryloyl-(L)-glutamic acid is as follows: by weight, 4.0-6.0 parts of L-glutamic acid-5-methyl ester and 0.10-0.25 parts of hydroquinone are dissolved in 100 parts of dichloromethane, mixed evenly and the solution is cooled to -5-0°C, then 10-15 parts of triethylamine are added to the solution, 3.0-5.0 parts of methacryloyl chloride are slowly poured into the solution under a nitrogen atmosphere, the solution is magnetically stirred at room temperature for 90-120 minutes, and after the reaction is completed, the unreacted methacryloyl chloride is extracted with 10wt.% NaOH, and then the extracted solution is evaporated in a rotary evaporator for 10-14 hours to finally obtain N-methacryloyl-(L)-glutamic acid.
[0009] The present invention adopts the design of nanoparticles loaded with acetyl octapeptide-3, which is mainly used to enhance the stability, transdermal absorption efficiency and long-term sustained release performance of bioactive peptides. By preparing glutamine-based nanoparticles and loading acetyl octapeptide-3, the active peptide molecules are effectively embedded in the nanocarrier, giving it higher environmental adaptability and functional stability. The glutamine-based nanoparticles are prepared by emulsion polymerization, and its cross-linked structure is jointly constructed by hydroxyethyl methacrylate, N-methacryloyl-(L)-glutamic acid and ethylene glycol dimethacrylate, which ensures the mechanical strength and stability of the nanoparticles and provides good biocompatibility. By controlling the oxygen concentration and reaction conditions of the emulsion polymerization system, a uniformly distributed nanoparticle structure is formed, providing an ideal carrier platform for subsequent peptide molecule loading. During the loading process, the acetyl octapeptide-3 solution maintains a suitable pH value under the action of a citric acid buffer to ensure the active integrity of the peptide molecules during the loading process, and the low-speed stirring and centrifugal operation further optimize the uniform distribution of the peptide molecules on the surface of the nanoparticles, thereby improving the loading efficiency and stability of the peptide molecules. In addition, through liquid nitrogen freezing and freeze-drying steps, dry loaded acetyl octapeptide-3 nanoparticles were finally formed, laying the foundation for the subsequent long-term release. In particular, the glutamine-based structure of the nanoparticles can slowly degrade in the skin environment and gradually release the embedded peptide molecules, thereby prolonging the action time of the active peptides and achieving the goal of long-term sustained release. Through this design scheme, a highly synergistic mechanism of action is formed between the components. The physical stability, chemical compatibility and sustained release function of the glutamine-based nanoparticles work together with the biological activity of acetyl octapeptide-3. At the same time, combined with the pH adjustment ability of the citric acid buffer and the optimization of the drying process, the efficient release and stability improvement of the bioactive peptides in the complex skin environment are achieved, providing important technical support for the research and development of anti-aging and firming skin care products.
[0010] Furthermore, the preparation method of the copper-peptide nanolipid complex is as follows: 5.0-10.0 parts of soybean lecithin and 5.0-10.0 parts of cholesterol are added to 200 parts of polyethylene glycol 400, and stirred at 50-70°C for 30-45 minutes; then the mixed solution is cooled to 5-10°C, and then 2.0-5.0 parts of 0.2wt.% copper peptide aqueous solution are added thereto, and the mixed solution is stirred in a high-speed homogenizer at 8000-9000rpm for 5.0-10 minutes; then the mixed solution is subjected to high-pressure treatment at a pressure of 1000 bar for 10-15 minutes, and finally the complex solution is placed in a freeze dryer and dried for 20-24 hours to obtain the copper-peptide nanolipid complex.
[0011] The present invention adopts the design of copper peptide nanolipid complex mainly for enhancing the stability, transdermal absorption efficiency and long-term sustained release performance of active peptides. By constructing nanoliposomes with soybean lecithin and cholesterol as the main components, the carrier is endowed with excellent membrane structure stability and biocompatibility, and an ideal carrier environment is provided for the encapsulation and protection of copper peptides. In the preparation process, soybean lecithin and cholesterol are mixed in polyethylene glycol 400 and heated and stirred to form a stable lipid bilayer structure, which can simulate the characteristics of biological membranes, thereby improving the skin permeability of copper peptides. Through the cooling operation of the solution, the copper peptide aqueous solution is added to the liposome solution, which effectively avoids the degradation phenomenon that may occur in copper peptides under high temperature conditions and ensures its biological activity. Subsequently, high-speed homogenization treatment causes the copper peptide molecules to be evenly distributed inside or on the surface of the liposomes, further improving the dispersion stability and loading efficiency of the complex. Through high-pressure treatment, the particle size of the complex is further reduced to form a nano-scale lipid complex, which not only significantly improves the transdermal absorption capacity of the copper peptide, but also enhances its environmental adaptability and storage stability in practical applications. Finally, the lipid complex is converted into a stable dry powder state through freeze-drying technology, which further extends the storage life of the product and provides convenience for subsequent use. The synergistic effect of soybean lecithin and cholesterol in the formation of liposomes not only gives the complex good physical stability, but also enhances the sustained release performance of copper peptides by optimizing the membrane structure, so that it can be gradually released in the skin environment, thereby prolonging the action time and enhancing the anti-aging effect. In summary, the present invention significantly improves the stability, transdermal absorption efficiency and long-term effect of active peptides in complex skin environments through the synergistic effect of the stable structural design of liposomes, the efficient loading of copper peptides and the sustained release mechanism, providing important technical support for the development of high-performance anti-aging skin care products.
[0012] The present invention also provides a method for preparing a composite anti-aging and skin-tightening polypeptide skin care product, comprising the following steps: S1. Prepare the aqueous phase: add 60% of the total weight of deionized water into a stirring container, stir at room temperature at a stirring rate of 300-500 rpm, add carbomer, xanthan gum, disodium EDTA, sodium ascorbyl phosphate and triethanolamine in sequence, and stir for 30-40 minutes until all components are completely dissolved to form a uniform and transparent aqueous phase solution.
[0013] S2. Prepare the oil phase: Add squalane, caprylic / capric triglyceride, cholesterol, phospholipids, ceramide and polysorbate-60 into another container, slowly heat to 50-70°C, and stir at a stirring rate of 200-400 rpm for 20-30 min until the components are completely mixed to form a uniform oil phase solution.
[0014] S3. Preparation of active ingredients: Prepare nanoparticle suspension, polypeptide active solution, moisturizing solution and antioxidant solution respectively.
[0015] S4. Emulsification process: slowly add the oil phase prepared in step S2 to the water phase in step S1, emulsify in a high-speed emulsifier at an emulsification rate of 5000-6000 rpm, and maintain the temperature at 50-70°C for 20-30 minutes until a stable emulsion is formed.
[0016] S5. Prepare the finished product: slowly add the nanoparticle suspension, polypeptide active solution, moisturizing solution, antioxidant solution and citric acid-sodium citrate buffer prepared in step S3 to the emulsion in sequence, and control the addition speed to be 12 mL / min. After the addition is completed, stir at a stirring rate of 300-500 rpm for 30-45 minutes in the range of 40-50°C; after the stirring is completed, the emulsion is naturally cooled to room temperature, and phenoxyethanol, ethylhexylglycerin and seaweed extract are slowly added, and the stirring is continued at a stirring rate of 150-250 rpm for 10-15 minutes to mix evenly; then the emulsion is placed in a vacuum degassing machine, and degassed under a vacuum condition of -0.08~-0.1 MPa for 10~15 minutes to remove residual bubbles in the emulsion. After the degassing is completed, the emulsion is placed in a clean container and sealed for storage to finally obtain a compound anti-aging and firming polypeptide skin care product.
[0017] Furthermore, the preparation method of the nanoparticle suspension in step S3 is: dispersing the loaded acetyl octapeptide-3 nanoparticles in 10% of the total mass of deionized water, stirring at a stirring rate of 100-200 rpm for 10-20 minutes until a uniform nanoparticle suspension is formed.
[0018] Furthermore, the preparation method of the polypeptide active solution in step S3 is: dissolving the copper peptide nanolipid complex and palmitoyl pentapeptide-4 in 10% of the total mass of deionized water, stirring at a stirring rate of 150-250 rpm for 10-15 minutes until completely dissolved to form a polypeptide active solution.
[0019] Furthermore, the preparation method of the moisturizing solution in step S3 is: dissolving sodium hyaluronate, glycerin, butylene glycol, propylene glycol and panthenol in 20% of the total mass of deionized water, respectively, and stirring at a stirring rate of 200-300 rpm for 15-20 minutes to form a uniform moisturizing solution.
[0020] Furthermore, the preparation method of the antioxidant solution in step S3 is: dissolving vitamin E, coenzyme Q10 and resveratrol in an appropriate amount of an oil phase solvent, stirring at a stirring rate of 250-350 rpm for 10-15 minutes until they are fully dissolved to form a uniform antioxidant solution.
[0021] The present invention adopts the design of compound anti-aging firming polypeptide skin care products, which is mainly used to enhance the anti-aging performance, firming effect and multiple functions of skin care products, and realizes the synergistic effect of each component through scientific component design and optimization process. Carbomer, xanthan gum and the like in the aqueous phase provide the stability and viscosity of the emulsion, ceramide repairs the skin barrier and enhances the moisturizing performance; squalane, cholesterol and the like in the oil phase simulate the lipid structure of the skin to improve the permeability and stability of the emulsion. During the emulsification process, a uniform and stable emulsion is formed by high-speed emulsification technology, providing an ideal matrix for the subsequent addition of active components. The copper peptide nanolipid complex and palmitoyl pentapeptide-4 in the polypeptide active solution synergistically promote collagen production and tighten the skin; the loaded acetyl octapeptide-3 in the nanoparticle suspension realizes sustained release and prolongs the anti-wrinkle effect; the moisturizing solution and the antioxidant solution respectively enhance the moisturizing and antioxidant properties. Finally, the quality of the emulsion is improved by vacuum degassing, and the synergistic effect of each component significantly improves the stability, transdermal absorption efficiency and multifunctionality of the skin care products, providing technical support for the research and development of high-end anti-aging skin care products.
[0022] In the compound anti-aging and firming polypeptide skin care product of the present invention, the synergistic effect of various components realizes multiple functions: the loaded acetyl octapeptide-3 nanoparticles prolong the anti-wrinkle effect through a sustained release mechanism, the copper peptide nanolipid complex and palmitoyl pentapeptide-4 synergistically promote collagen production and enhance the firming effect; sodium hyaluronate, glycerol, butylene glycol and propylene glycol jointly provide deep moisturizing, repair the skin barrier and improve skin quality; squalane, caprylic / capric triglyceride and phospholipids simulate the lipid structure of the skin to enhance the permeability and stability of the product; carbomer, xanthan gum and triethanolamine enhance the viscosity and stability of the emulsion , providing support for the uniform dispersion of active ingredients; vitamin E, coenzyme Q10 and resveratrol are highly effective antioxidants, working in synergy with sodium ascorbyl phosphate to scavenge free radicals and reduce oxidative damage; ceramide and cholesterol repair the skin barrier and enhance the skin's moisturizing ability; panthenol and seaweed extract soothe and repair the skin, improving the mildness of the product; phenoxyethanol and ethylhexylglycerin provide safe and efficient preservative protection while optimizing the stability of the formula; disodium EDTA chelates metal ions to prevent degradation of active ingredients; citric acid-sodium citrate buffer adjusts the pH value to ensure that the product is mild and suitable for a variety of skin types. Through functional complementarity and synergy, each component not only gives the product significant anti-aging and firming effects, but also has moisturizing, antioxidant and repair functions to meet multi-level skin care needs.
[0023] (2) Beneficial technical effects 1. The present invention significantly improves the stability, transdermal absorption efficiency and long-term release performance of active peptides through the innovative design of loaded acetyl octapeptide-3 nanoparticles, solving the problems of poor stability and uneven release of active peptides in the prior art. The high mechanical strength and sustained-release ability of glutamine-based nanoparticles synergize with the biological activity of acetyl octapeptide-3, combined with the pH adjustment of citric acid buffer and freeze-drying process, ensures efficient collaboration between components and prolonged action time, has good environmental adaptability and application prospects, and provides breakthrough technical support for anti-aging skin care products.
[0024] 2. The present invention significantly improves the stability, transdermal absorption efficiency and long-term release performance of active peptides through the innovative design of copper peptide nanolipid complexes, solving the problems of easy degradation and low absorption efficiency of active peptides in traditional technologies. Soy lecithin and cholesterol synergistically construct a stable lipid bilayer structure, enhancing membrane stability and sustained release capacity. High-speed homogenization and high-pressure treatment further optimize the particle size and distribution of nanoparticles, improving active loading efficiency and absorption performance; freeze-drying technology extends the storage life of the product and ensures biological activity. The components achieve synergy through precise proportioning and optimized processes, providing an efficient, stable and safe technical solution for the research and development of anti-aging skin care products.
[0025] 3. The present invention significantly improves the anti-aging performance and skin tightening effect through the innovative design of the compound anti-aging and skin tightening polypeptide skin care products, and solves the problems of poor stability and low absorption efficiency of skin care products in the prior art. The aqueous phase component provides emulsion stability, the oil phase component simulates the lipid structure of the skin to enhance permeability, the polypeptide active solution and the nanoparticle suspension synergistically promote collagen production and prolong the sustained release effect, and the moisturizing and antioxidant solution further optimizes the moisturizing and antioxidant properties. Through precise proportioning and optimized process, the synergistic effect of each component achieves multifunctionality and efficient absorption, providing breakthrough technical support for the research and development of high-end skin care products.
[0026] 4. The present invention significantly improves the anti-aging, firming, moisturizing and antioxidant properties of skin care products through the precise proportion and synergistic effect of each component, solving the problems of scattered efficacy and poor stability in the prior art. Acetyl octapeptide-3 is loaded to achieve sustained release anti-wrinkle, copper peptide nanolipid complex and palmitoyl pentapeptide-4 synergistically promote collagen synthesis, moisturizing factors such as sodium hyaluronate deeply moisturize the skin, lipid structures such as squalane enhance permeability and stability, and antioxidant components effectively reduce oxidative damage. By optimizing the process, the functions of each component are complementary, significantly improving product performance, and providing technical support for the research and development of high-end skin care products. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a morphology diagram of the glutamine-based nanoparticles prepared in Example 1 of the present invention.
[0028] Figure 2 This is a morphology picture of the acetyl octapeptide-3 loaded nanoparticles prepared in Example 1 of the present invention.
[0029] Figure 3 This is the infrared Fourier spectrum of the glutamine-based nanoparticles prepared in Example 1 of the present invention.
[0030] Figure 4 This is the infrared Fourier spectrum of the acetyl octapeptide-3 loaded nanoparticles prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0032] Example 1
[0033] A compound anti-aging and firming polypeptide skin care product comprises the following components in weight fractions: 2.0 parts of loaded acetyl octapeptide-3 nanoparticles, 1.0 parts of copper peptide nanolipid complexes, 1.0 parts of palmitoyl pentapeptide-4, 0.5 parts of sodium hyaluronate, 3.0 parts of glycerol, 2.0 parts of butylene glycol, 2.0 parts of squalane, 1.0 parts of caprylic / capric triglyceride, 1.5 parts of polysorbate-60, 0.2 parts of carbomer, 0.1 parts of xanthan gum, 0.2 parts of triethanolamine, 0.5 parts of vitamin E, 0.5 parts of panthenol, 0.5 parts of seaweed extract, 0.6 parts of phenoxyethanol, 0.5 parts of ethylhexylglycerin, and coenzyme Q10. 0.5 parts, resveratrol 0.5 parts, ceramide 0.5 parts, cholesterol 0.2 parts, phospholipids 1.0 parts, disodium EDTA 0.1 parts, sodium ascorbyl phosphate 0.1 parts, propylene glycol 1.0 parts, deionized water 60.0 parts, citric acid-sodium citrate buffer 0.05 parts.
[0034] The loaded acetyl octapeptide-3 nanoparticles of this embodiment are composed of glutamine-based nanoparticles and acetyl octapeptide-3 loaded on the glutamine-based nanoparticles; the glutamine-based nanoparticles are prepared by copolymerization of hydroxyethyl methacrylate and N-methacryloyl-(L)-glutamic acid by emulsion polymerization; N-methacryloyl-(L)-glutamic acid is obtained by chlorination reaction of L-glutamic acid-5-methyl ester and methacryloyl chloride; the copper-peptide-lipid nanocomposite liposomes are prepared from copper peptides and nanoliposomes by emulsification combined with high-pressure homogenization technology; the pH of the polypeptide skin care product is 5.5.
[0035] The preparation method of the loaded acetyl octapeptide-3 nanoparticles in this embodiment is as follows: by weight, 2.0 parts of glutamine-based nanoparticles and 0.01 parts of sodium chloride are added to 30 parts of 0.4 mg / mL acetyl octapeptide-3 solution, the mixture is placed in a beaker, the stirring rate is 30 rpm, the stirring time is 20 min, and the pH of the solution is adjusted to 3.4 with a citric acid buffer during the stirring process. After the stirring is completed, the obtained nanoparticle suspension is transferred to a centrifuge and centrifuged at a speed of 10000 rpm for 20 min, the supernatant is discarded, and the nanoparticle precipitate is separated. The obtained precipitate is washed 3 times with deionized water, and the amount of each washing is twice the volume of the suspension. After the washing is completed, the washed nanoparticle suspension is frozen with liquid nitrogen and placed in a freeze dryer for 20 h to finally obtain loaded acetyl octapeptide-3 nanoparticles.
[0036] The preparation method of the glutamine-based nanoparticles of this embodiment is as follows: in parts by weight, deionized water is used as a solvent, 270.0 parts of polyvinyl alcohol are dissolved in 20.0 parts of deionized water, the mixture is placed in a beaker, the stirring rate is set to 300 rpm, the stirring time is 30 min, until a uniform mixed solution is formed, then 0.50 parts of hydroxyethyl methacrylate, 0.80 parts of N-methacryloyl-(L)-glutamic acid and 0.29 parts of ethylene glycol dimethacrylate crosslinking agent are added to the mixed solution in sequence, the stirring rate is 300 rpm, and the stirring is continued for 20 min until a uniform reaction solution is formed, 18.0 parts of 50wt.% potassium persulfate solution are slowly added dropwise to the reaction solution, and nitrogen is purged at a flow rate of 10.0 sccm for 240s to remove oxygen in the solution, the mixed solution is heated to 60°C at a heating rate of 2°C / min, and the stirring rate is maintained at 120 rpm for 240s under the heating condition. min, until the reaction is complete and an emulsion mixture is formed. After the reaction is completed, it is naturally cooled to room temperature. The cooled emulsion is transferred to a centrifuge and centrifuged at 11,000 rpm for 20 min to separate the precipitate and discard the supernatant. The obtained precipitate is washed alternately with anhydrous ethanol and deionized water for 3 times, each time with an amount twice that of the precipitate, to remove unreacted monomers and impurities. After washing, the precipitate is placed in a vacuum drying oven and dried at room temperature for 16 h to finally obtain glutamine-based nanoparticles.
[0037] The preparation method of N-methacryloyl-(L)-glutamic acid in this embodiment is as follows: by weight, 4.0 parts of L-glutamic acid-5-methyl ester and 0.10 parts of hydroquinone are dissolved in 100 parts of dichloromethane, mixed evenly, and the solution is cooled to -5°C, and then 10 parts of triethylamine are added to the solution, and 3.0 parts of methacryloyl chloride are slowly poured into the solution under a nitrogen atmosphere, and the solution is magnetically stirred at room temperature for 90 minutes. After the reaction is completed, unreacted methacryloyl chloride is extracted with 10 wt.% NaOH, and then the extracted solution is evaporated in a rotary evaporator for 10 hours to finally obtain N-methacryloyl-(L)-glutamic acid.
[0038] The preparation method of the copper-peptide nanolipid complex of this embodiment is as follows: 5.0 parts of soybean lecithin and 5.0 parts of cholesterol are added to 200 parts of polyethylene glycol 400, and stirred at 50°C for 30 minutes; the mixed solution is then cooled to 5°C, and then 2.0 parts of 0.2wt.% copper peptide aqueous solution are added thereto, and the mixed solution is stirred in a high-speed homogenizer at 8000 rpm for 5.0 minutes; the mixed solution is then subjected to high-pressure treatment at a pressure of 1000 bar for 10 minutes, and finally the complex solution is placed in a freeze dryer and dried for 20 hours to obtain the copper-peptide nanolipid complex.
[0039] A method for preparing a composite anti-aging and skin-tightening polypeptide skin care product of this embodiment comprises the following steps: S1. Prepare the aqueous phase: add 60% of the total weight of deionized water into a stirring container, stir at room temperature at a stirring rate of 300 rpm, add carbomer, xanthan gum, disodium EDTA, sodium ascorbyl phosphate and triethanolamine in sequence, and stir for 30 minutes until all components are completely dissolved to form a uniform and transparent aqueous phase solution.
[0040] S2. Prepare the oil phase: Add squalane, caprylic / capric triglyceride, cholesterol, phospholipids, ceramide and polysorbate-60 into another container, slowly heat to 50°C, and stir at a stirring rate of 200 rpm for 20 minutes until the components are completely mixed to form a uniform oil phase solution.
[0041] S3. Preparation of active ingredients: Nanoparticle suspension, peptide active solution, moisturizing solution and antioxidant solution were prepared respectively. The method for preparing the nanoparticle suspension is as follows: dispersing the loaded acetyl octapeptide-3 nanoparticles in 10% of the total mass of deionized water, stirring at a stirring rate of 100 rpm for 10 minutes until a uniform nanoparticle suspension is formed. The method for preparing the peptide active solution is as follows: dissolving the copper peptide nanolipid complex and palmitoyl pentapeptide-4 in 10% of the total mass of deionized water, stirring at a stirring rate of 150 rpm for 10 minutes until they are completely dissolved to form a peptide active solution. The method for preparing the moisturizing solution is as follows: dissolving sodium hyaluronate, glycerol, butylene glycol, propylene glycol and panthenol in 20% of the total mass of deionized water, stirring at a stirring rate of 200 rpm for 15 minutes to form a uniform moisturizing solution. The preparation method of the antioxidant solution is as follows: vitamin E, coenzyme Q10 and resveratrol are dissolved in an appropriate amount of an oil phase solvent, and stirred at a stirring rate of 250 rpm for 10 minutes until they are fully dissolved to form a uniform antioxidant solution.
[0042] S4. Emulsification process: slowly add the oil phase prepared in step S2 to the water phase in step S1, emulsify in a high-speed emulsifier at an emulsification rate of 5000 rpm, and maintain the temperature at 50°C for 20 minutes until a stable emulsion is formed.
[0043] S5. Prepare the finished product: slowly add the nanoparticle suspension, polypeptide active solution, moisturizing solution, antioxidant solution and citric acid-sodium citrate buffer prepared in step S3 to the emulsion in sequence, and control the addition speed to be 12 mL / min. After the addition is completed, stir at a stirring rate of 300 rpm for 30 minutes at a temperature of 40°C; after the stirring is completed, naturally cool the emulsion to room temperature, slowly add phenoxyethanol, ethylhexylglycerin and seaweed extract, and continue to stir at a stirring rate of 150 rpm for 10 minutes to mix evenly; then place the emulsion in a vacuum degassing machine, and degas under a vacuum condition of -0.08 MPa for 10 minutes to remove residual bubbles in the emulsion. After the degassing is completed, the emulsion is placed in a clean container and sealed for storage to finally obtain a compound anti-aging and firming polypeptide skin care product.
[0044] pass Figure 1 and Figure 2 It can be intuitively observed that the glutamine-based nanoparticles prepared in Example 1 of the present invention have a uniform morphology, and the surface of the nanoparticles loaded with acetyl octapeptide-3 is successfully loaded with acetyl octapeptide-3 particles, indicating that the preparation method of the present invention is feasible and effective in constructing nanoparticles and loading active polypeptides. Figure 3 and Figure 4 The infrared Fourier spectrum analysis shows that the two -¹ and 1548 cm - The typical absorption bands of amide I and amide II appeared at 1721 cm - The characteristic peak at ¹ comes from the carbonyl structure of glutamic acid in the N-methylacryloyl-(L)-glutamic acid monomer, which further verifies the structural integrity and component characteristics of the glutamine-based nanoparticles. This comprehensively proves the rationality and effectiveness of the nanoparticles prepared by the present invention and their loading functions.
[0045] Example 2
[0046] A compound anti-aging and firming polypeptide skin care product comprises the following components in weight fractions: 2.9 parts of loaded acetyl octapeptide-3 nanoparticles, 1.3 parts of copper peptide nanolipid complexes, 1.6 parts of palmitoyl pentapeptide-4, 0.8 parts of sodium hyaluronate, 3.6 parts of glycerol, 2.6 parts of butylene glycol, 2.6 parts of squalane, 1.6 parts of caprylic / capric triglyceride, 1.9 parts of polysorbate-60, 0.3 parts of carbomer, 0.2 parts of xanthan gum, 0.2 parts of triethanolamine, 0.7 parts of vitamin E, 0.7 parts of panthenol, 0.7 parts of seaweed extract, 0.7 parts of phenoxyethanol, 0.7 parts of ethylhexylglycerin, and coenzyme Q10. 0.7 parts, resveratrol 0.6 parts, ceramide 0.7 parts, cholesterol 0.3 parts, phospholipids 1.3 parts, disodium EDTA 0.2 parts, sodium ascorbyl phosphate 0.1 parts, propylene glycol 1.3 parts, deionized water 61.5 parts, citric acid-sodium citrate buffer 0.1 parts.
[0047] The loaded acetyl octapeptide-3 nanoparticles of this embodiment are composed of glutamine-based nanoparticles and acetyl octapeptide-3 loaded on the glutamine-based nanoparticles; the glutamine-based nanoparticles are prepared by copolymerization of hydroxyethyl methacrylate and N-methacryloyl-(L)-glutamic acid by emulsion polymerization; N-methacryloyl-(L)-glutamic acid is obtained by chlorination reaction of L-glutamic acid-5-methyl ester and methacryloyl chloride; the copper-peptide-lipid nanocomposite liposomes are prepared from copper peptides and nanoliposomes by emulsification combined with high-pressure homogenization technology; the pH of the polypeptide skin care product is 5.2.
[0048] The preparation method of the loaded acetyl octapeptide-3 nanoparticles in this embodiment is as follows: by weight, 2.9 parts of glutamine-based nanoparticles and 0.01 parts of sodium chloride are added to 33 parts of 0.4 mg / mL acetyl octapeptide-3 solution, the mixture is placed in a beaker, the stirring rate is 33 rpm, the stirring time is 26 min, and the pH of the solution is adjusted to 4.2 with a citric acid buffer during the stirring process. After the stirring is completed, the obtained nanoparticle suspension is transferred to a centrifuge and centrifuged at a speed of 10600 rpm for 21 min, the supernatant is discarded, and the nanoparticle precipitate is separated. The obtained precipitate is washed 3 times with deionized water, and the amount of each washing is twice the volume of the suspension. After the washing is completed, the washed nanoparticle suspension is frozen with liquid nitrogen and placed in a freeze dryer for 21 h to finally obtain loaded acetyl octapeptide-3 nanoparticles.
[0049] The preparation method of the glutamine-based nanoparticles of this embodiment is as follows: in parts by weight, deionized water is used as a solvent, 273 parts of polyvinyl alcohol are dissolved in 23 parts of deionized water, the mixture is placed in a beaker, the stirring rate is set to 315 rpm, and the stirring time is 33 min until a uniform mixed solution is formed, then 0.55 parts of hydroxyethyl methacrylate, 0.89 parts of N-methacryloyl-(L)-glutamic acid and 0.30 parts of ethylene glycol dimethacrylate crosslinking agent are added to the mixed solution in sequence, the stirring rate is 315 rpm, and the stirring is continued for 23 min until a uniform reaction solution is formed, 18.6 parts of 50 wt.% potassium persulfate solution are slowly added dropwise to the reaction solution, and nitrogen is purged at a flow rate of 10.6 sccm for 276 s to remove oxygen in the solution, the mixed solution is heated to 63°C at a heating rate of 2°C / min, and the stirring rate is maintained at 129 rpm for 258 s under the heating condition. min, until the reaction is complete and an emulsion mixture is formed. After the reaction is completed, it is naturally cooled to room temperature. The cooled emulsion is transferred to a centrifuge and centrifuged at 11300 rpm for 21 min to separate the precipitate and discard the supernatant. The obtained precipitate is washed alternately with anhydrous ethanol and deionized water for 4 times, each time with an amount twice that of the precipitate, to remove unreacted monomers and impurities. After washing, the precipitate is placed in a vacuum drying oven and dried at room temperature for 17 h to finally obtain glutamine-based nanoparticles.
[0050] The preparation method of N-methacryloyl-(L)-glutamic acid in this embodiment is as follows: by weight, 4.6 parts of L-glutamic acid-5-methyl ester and 0.15 parts of hydroquinone are dissolved in 100 parts of dichloromethane, mixed evenly, and the solution is cooled to -3.5°C, and then 11.5 parts of triethylamine are added to the solution, and 3.6 parts of methacryloyl chloride are slowly poured into the solution under a nitrogen atmosphere, and the solution is magnetically stirred at room temperature for 99 minutes. After the reaction is completed, unreacted methacryloyl chloride is extracted with 10 wt.% NaOH, and then the extracted solution is evaporated in a rotary evaporator for 11 hours to finally obtain N-methacryloyl-(L)-glutamic acid.
[0051] The preparation method of the copper-peptide nanolipid complex of this embodiment is as follows: 6.5 parts of soybean lecithin and 6.5 parts of cholesterol are added to 200 parts of polyethylene glycol 400, and stirred at 56°C for 34 minutes; the mixed solution is then cooled to 6.5°C, and then 2.9 parts of 0.2wt.% copper peptide aqueous solution are added thereto, and the mixed solution is stirred in a high-speed homogenizer at 8300 rpm for 6.5 minutes; the mixed solution is then subjected to high-pressure treatment at a pressure of 1000 bar for 11.5 minutes, and finally the complex solution is placed in a freeze dryer and dried for 21 hours to obtain the copper-peptide nanolipid complex.
[0052] A method for preparing a composite anti-aging and skin-tightening polypeptide skin care product of this embodiment comprises the following steps: S1. Prepare the aqueous phase: add 60% of the total weight of deionized water into a stirring container, stir at room temperature at a stirring rate of 360 rpm, add carbomer, xanthan gum, disodium EDTA, sodium ascorbyl phosphate and triethanolamine in sequence, and stir for 33 minutes until all components are completely dissolved to form a uniform and transparent aqueous phase solution.
[0053] S2. Prepare the oil phase: Add squalane, caprylic / capric triglyceride, cholesterol, phospholipids, ceramide and polysorbate-60 into another container, slowly heat to 56°C, and stir at a stirring rate of 260 rpm for 23 minutes until the components are completely mixed to form a uniform oil phase solution.
[0054] S3. Preparation of active ingredients: Prepare nanoparticle suspension, peptide active solution, moisturizing solution and antioxidant solution respectively. The preparation method of nanoparticle suspension is as follows: disperse the loaded acetyl octapeptide-3 nanoparticles in 10% of the total mass of deionized water, stir at a stirring rate of 130 rpm for 13 minutes, until a uniform nanoparticle suspension is formed. The preparation method of peptide active solution is as follows: dissolve the copper peptide nanolipid complex and palmitoyl pentapeptide-4 in 10% of the total mass of deionized water, stir at a stirring rate of 180 rpm for 11.5 minutes, until completely dissolved, to form a peptide active solution. The preparation method of moisturizing solution is as follows: dissolve sodium hyaluronate, glycerol, butylene glycol, propylene glycol and panthenol in 20% of the total mass of deionized water, stir at a stirring rate of 230 rpm for 16.5 minutes, to form a uniform moisturizing solution. The preparation method of the antioxidant solution is as follows: vitamin E, coenzyme Q10 and resveratrol are dissolved in an appropriate amount of an oil phase solvent, and stirred at a stirring rate of 280 rpm for 11.5 minutes until they are fully dissolved to form a uniform antioxidant solution.
[0055] S4. Emulsification process: The oil phase prepared in step S2 is slowly added to the water phase in step S1, and emulsified in a high-speed emulsifier at an emulsification rate of 5300 rpm, and the temperature is maintained at 56° C. The emulsification time is 23 min until a stable emulsion is formed.
[0056] S5. Prepare the finished product: slowly add the nanoparticle suspension, polypeptide active solution, moisturizing solution, antioxidant solution and citric acid-sodium citrate buffer prepared in step S3 to the emulsion in sequence, and control the addition speed to be 12 mL / min. After the addition is completed, stir at a stirring rate of 360 rpm for 34 minutes at a temperature of 43°C; after the stirring is completed, naturally cool the emulsion to room temperature, slowly add phenoxyethanol, ethylhexylglycerin and seaweed extract, and continue to stir at a stirring rate of 180 rpm for 11.5 minutes to mix evenly; then place the emulsion in a vacuum degassing machine, and degas under a vacuum condition of -0.09 MPa for 11.5 minutes to remove residual bubbles in the emulsion. After the degassing is completed, the emulsion is placed in a clean container and sealed for storage to finally obtain a compound anti-aging and firming polypeptide skin care product.
[0057] Example 3
[0058] A compound anti-aging and firming polypeptide skin care product comprises the following components in weight fractions: 3.8 parts of loaded acetyl octapeptide-3 nanoparticles, 1.6 parts of copper peptide nanolipid complexes, 2.2 parts of palmitoyl pentapeptide-4, 1.1 parts of sodium hyaluronate, 4.2 parts of glycerol, 3.2 parts of butylene glycol, 3.2 parts of squalane, 2.2 parts of caprylic / capric triglyceride, 2.4 parts of polysorbate-60, 0.3 parts of carbomer, 0.2 parts of xanthan gum, 0.3 parts of triethanolamine, 0.8 parts of vitamin E, 0.8 parts of panthenol, 0.8 parts of seaweed extract, 0.7 parts of phenoxyethanol, 0.8 parts of ethylhexylglycerin, and coenzyme Q10. 0.8 parts, resveratrol 0.7 parts, ceramide 0.8 parts, cholesterol 0.4 parts, phospholipids 1.6 parts, disodium EDTA 0.2 parts, sodium ascorbyl phosphate 0.2 parts, propylene glycol 1.6 parts, deionized water 63.0 parts, citric acid-sodium citrate buffer 0.1 parts.
[0059] The loaded acetyl octapeptide-3 nanoparticles of this embodiment are composed of glutamine-based nanoparticles and acetyl octapeptide-3 loaded on the glutamine-based nanoparticles; the glutamine-based nanoparticles are prepared by copolymerization of hydroxyethyl methacrylate and N-methacryloyl-(L)-glutamic acid by emulsion polymerization; N-methacryloyl-(L)-glutamic acid is obtained by chlorination reaction of L-glutamic acid-5-methyl ester and methacryloyl chloride; the copper-peptide-lipid nanocomposite liposomes are prepared from copper peptides and nanoliposomes by emulsification combined with high-pressure homogenization technology; the pH of the polypeptide skin care product is 4.8.
[0060] The preparation method of the loaded acetyl octapeptide-3 nanoparticles in this embodiment is as follows: by weight, 3.8 parts of glutamine-based nanoparticles and 0.02 parts of sodium chloride are added to 36 parts of 0.4 mg / mL acetyl octapeptide-3 solution, the mixture is placed in a beaker, the stirring rate is 36 rpm, the stirring time is 32 min, and the pH of the solution is adjusted to 5.0 with a citric acid buffer during the stirring process. After the stirring is completed, the obtained nanoparticle suspension is transferred to a centrifuge and centrifuged at a speed of 11200 rpm for 23 min, the supernatant is discarded, and the nanoparticle precipitate is separated. The obtained precipitate is washed 3 times with deionized water, and the amount of each washing is twice the volume of the suspension. After the washing is completed, the washed nanoparticle suspension is frozen with liquid nitrogen and placed in a freeze dryer for 22 h to finally obtain loaded acetyl octapeptide-3 nanoparticles.
[0061] The preparation method of the glutamine-based nanoparticles of this embodiment is as follows: in parts by weight, deionized water is used as a solvent, 276.0 parts of polyvinyl alcohol are dissolved in 26.0 parts of deionized water, the mixture is placed in a beaker, the stirring rate is set to 330 rpm, and the stirring time is 36 min until a uniform mixed solution is formed, then 0.59 parts of hydroxyethyl methacrylate, 0.98 parts of N-methacryloyl-(L)-glutamic acid and 0.30 parts of ethylene glycol dimethacrylate crosslinking agent are added to the above mixed solution in sequence, the stirring rate is 330 rpm, and the stirring is continued for 26 min until a uniform reaction solution is formed, 19.2 parts of 50wt.% potassium persulfate solution are slowly added dropwise to the above reaction solution, and nitrogen is purged for 312s at a flow rate of 11.2 sccm to remove oxygen in the solution, the mixed solution is heated to 66°C at a heating rate of 2°C / min, and the stirring rate is maintained at 138 rpm for 276 min, until the reaction is complete and an emulsion mixture is formed. After the reaction is completed, it is naturally cooled to room temperature. The cooled emulsion is transferred to a centrifuge and centrifuged at 11600 rpm for 23 min. The precipitate is separated and the supernatant is discarded. The obtained precipitate is washed alternately with anhydrous ethanol and deionized water for 4 times, each time with an amount twice that of the precipitate, to remove unreacted monomers and impurities. After washing, the precipitate is placed in a vacuum drying oven and dried at room temperature for 18 h to finally obtain glutamine-based nanoparticles.
[0062] The preparation method of N-methacryloyl-(L)-glutamic acid in this embodiment is as follows: by weight, 5.2 parts of L-glutamic acid-5-methyl ester and 0.19 parts of hydroquinone are dissolved in 100 parts of dichloromethane, mixed evenly, and the solution is cooled to -3°C, and then 13 parts of triethylamine are added to the solution, and 4.2 parts of methacryloyl chloride are slowly poured into the solution under a nitrogen atmosphere, and the solution is magnetically stirred at room temperature for 108 minutes. After the reaction is completed, unreacted methacryloyl chloride is extracted with 10 wt.% NaOH, and then the extracted solution is evaporated in a rotary evaporator for 12 hours to finally obtain N-methacryloyl-(L)-glutamic acid.
[0063] The preparation method of the copper-peptide nanolipid complex of this embodiment is as follows: 8.0 parts of soybean lecithin and 8.0 parts of cholesterol are added to 200 parts of polyethylene glycol 400, and stirred at 62°C for 39 minutes; the mixed solution is then cooled to 8°C, and then 3.8 parts of 0.2wt.% copper peptide aqueous solution are added thereto, and the mixed solution is stirred in a high-speed homogenizer at 8600 rpm for 8 minutes; the mixed solution is then subjected to high-pressure treatment at a pressure of 1000 bar for 13 minutes, and finally the complex solution is placed in a freeze dryer and dried for 22 hours to obtain the copper-peptide nanolipid complex.
[0064] A method for preparing a composite anti-aging and skin-tightening polypeptide skin care product of this embodiment comprises the following steps: S1. Prepare the aqueous phase: add 60% of the total weight of deionized water into a stirring container, stir at room temperature at a stirring rate of 420 rpm, add carbomer, xanthan gum, disodium EDTA, sodium ascorbyl phosphate and triethanolamine in sequence, stir for 36 minutes until all components are completely dissolved to form a uniform and transparent aqueous phase solution, and then.
[0065] S2. Prepare the oil phase: Add squalane, caprylic / capric triglyceride, cholesterol, phospholipids, ceramide and polysorbate-60 into another container, slowly heat to 62°C, and stir at a stirring rate of 320 rpm for 26 minutes until the components are completely mixed to form a uniform oil phase solution.
[0066] S3. Preparation of active ingredients: Nanoparticle suspension, peptide active solution, moisturizing solution and antioxidant solution were prepared respectively. The method for preparing the nanoparticle suspension is as follows: dispersing the loaded acetyl octapeptide-3 nanoparticles in 10% of the total mass of deionized water, stirring at a stirring rate of 160 rpm for 16 minutes until a uniform nanoparticle suspension is formed. The method for preparing the peptide active solution is as follows: dissolving the copper peptide nanolipid complex and palmitoyl pentapeptide-4 in 10% of the total mass of deionized water, stirring at a stirring rate of 210 rpm for 13 minutes until they are completely dissolved to form a peptide active solution. The method for preparing the moisturizing solution is as follows: dissolving sodium hyaluronate, glycerin, butylene glycol, propylene glycol and panthenol in 20% of the total mass of deionized water, stirring at a stirring rate of 260 rpm for 18 minutes to form a uniform moisturizing solution. The preparation method of the antioxidant solution is as follows: vitamin E, coenzyme Q10 and resveratrol are dissolved in an appropriate amount of an oil phase solvent, and stirred at a stirring rate of 310 rpm for 13 minutes until they are fully dissolved to form a uniform antioxidant solution.
[0067] S4. Emulsification process: The oil phase prepared in step S2 is slowly added to the water phase in step S1, and emulsified in a high-speed emulsifier at an emulsification rate of 5600 rpm, and the temperature is maintained at 62° C. The emulsification time is 26 min until a stable emulsion is formed.
[0068] S5. Prepare the finished product: slowly add the nanoparticle suspension, polypeptide active solution, moisturizing solution, antioxidant solution and citric acid-sodium citrate buffer prepared in step S3 to the emulsion in sequence, and control the addition speed to be 12 mL / min. After the addition is completed, stir at a stirring rate of 420 rpm for 39 minutes at a temperature of 46°C; after the stirring is completed, naturally cool the emulsion to room temperature, slowly add phenoxyethanol, ethylhexylglycerin and seaweed extract, and continue to stir at a stirring rate of 210 rpm for 13 minutes to mix evenly; then place the emulsion in a vacuum degassing machine, and degas under a vacuum condition of -0.09 MPa for 13 minutes to remove residual bubbles in the emulsion. After the degassing is completed, the emulsion is placed in a clean container and sealed for storage to finally obtain a compound anti-aging and firming polypeptide skin care product.
[0069] Example 4
[0070] A compound anti-aging and firming polypeptide skin care product comprises the following components in weight fractions: 3.8 parts of loaded acetyl octapeptide-3 nanoparticles, 1.6 parts of copper peptide nanolipid complexes, 2.2 parts of palmitoyl pentapeptide-4, 1.1 parts of sodium hyaluronate, 4.2 parts of glycerol, 3.2 parts of butylene glycol, 3.2 parts of squalane, 2.2 parts of caprylic / capric triglyceride, 2.4 parts of polysorbate-60, 0.3 parts of carbomer, 0.2 parts of xanthan gum, 0.3 parts of triethanolamine, 0.8 parts of vitamin E, 0.8 parts of panthenol, 0.8 parts of seaweed extract, 0.7 parts of phenoxyethanol, 0.8 parts of ethylhexylglycerin, and coenzyme Q10. 0.8 parts, resveratrol 0.7 parts, ceramide 0.8 parts, cholesterol 0.4 parts, phospholipids 1.6 parts, disodium EDTA 0.2 parts, sodium ascorbyl phosphate 0.2 parts, propylene glycol 1.6 parts, deionized water 63.0 parts, citric acid-sodium citrate buffer 0.1 parts.
[0071] The loaded acetyl octapeptide-3 nanoparticles of this embodiment are composed of glutamine-based nanoparticles and acetyl octapeptide-3 loaded on the glutamine-based nanoparticles; the glutamine-based nanoparticles are prepared by copolymerization of hydroxyethyl methacrylate and N-methacryloyl-(L)-glutamic acid by emulsion polymerization; N-methacryloyl-(L)-glutamic acid is obtained by chlorination reaction of L-glutamic acid-5-methyl ester and methacryloyl chloride; the copper-peptide-lipid nanocomposite liposomes are prepared from copper peptides and nanoliposomes by emulsification combined with high-pressure homogenization technology; the pH of the polypeptide skin care product is 4.5.
[0072] The preparation method of the loaded acetyl octapeptide-3 nanoparticles in this embodiment is as follows: by weight, 3.8 parts of glutamine-based nanoparticles and 0.02 parts of sodium chloride are added to 36 parts of 0.4 mg / mL acetyl octapeptide-3 solution, the mixture is placed in a beaker, the stirring rate is 36 rpm, the stirring time is 32 min, and the pH of the solution is adjusted to 5.0 with a citric acid buffer during the stirring process. After the stirring is completed, the obtained nanoparticle suspension is transferred to a centrifuge and centrifuged at a speed of 11200 rpm for 23 min, the supernatant is discarded, and the nanoparticle precipitate is separated. The obtained precipitate is washed 3 times with deionized water, and the amount of each washing is twice the volume of the suspension. After the washing is completed, the washed nanoparticle suspension is frozen with liquid nitrogen and placed in a freeze dryer for 22 h to finally obtain loaded acetyl octapeptide-3 nanoparticles.
[0073] The preparation method of the glutamine-based nanoparticles of this embodiment is as follows: in parts by weight, deionized water is used as a solvent, 276.0 parts of polyvinyl alcohol are dissolved in 26.0 parts of deionized water, the mixture is placed in a beaker, the stirring rate is set to 330 rpm, and the stirring time is 36 min until a uniform mixed solution is formed, then 0.59 parts of hydroxyethyl methacrylate, 0.98 parts of N-methacryloyl-(L)-glutamic acid and 0.30 parts of ethylene glycol dimethacrylate crosslinking agent are added to the above mixed solution in sequence, the stirring rate is 330 rpm, and the stirring is continued for 26 min until a uniform reaction solution is formed, 19.2 parts of 50wt.% potassium persulfate solution are slowly added dropwise to the above reaction solution, and nitrogen is purged for 312s at a flow rate of 11.2 sccm to remove oxygen in the solution, the mixed solution is heated to 66°C at a heating rate of 2°C / min, and the stirring rate is maintained at 138 rpm for 276 min, until the reaction is complete and an emulsion mixture is formed. After the reaction is completed, it is naturally cooled to room temperature. The cooled emulsion is transferred to a centrifuge and centrifuged at 11600 rpm for 23 min. The precipitate is separated and the supernatant is discarded. The obtained precipitate is washed alternately with anhydrous ethanol and deionized water for 4 times, each time with an amount twice that of the precipitate, to remove unreacted monomers and impurities. After washing, the precipitate is placed in a vacuum drying oven and dried at room temperature for 18 h to finally obtain glutamine-based nanoparticles.
[0074] The preparation method of N-methacryloyl-(L)-glutamic acid in this embodiment is as follows: by weight, 5.2 parts of L-glutamic acid-5-methyl ester and 0.19 parts of hydroquinone are dissolved in 100 parts of dichloromethane, mixed evenly, and the solution is cooled to -3°C, and then 13 parts of triethylamine are added to the solution, and 4.2 parts of methacryloyl chloride are slowly poured into the solution under a nitrogen atmosphere, and the solution is magnetically stirred at room temperature for 108 minutes. After the reaction is completed, unreacted methacryloyl chloride is extracted with 10 wt.% NaOH, and then the extracted solution is evaporated in a rotary evaporator for 12 hours to finally obtain N-methacryloyl-(L)-glutamic acid.
[0075] The preparation method of the copper-peptide nanolipid complex of this embodiment is as follows: 8.0 parts of soybean lecithin and 8.0 parts of cholesterol are added to 200 parts of polyethylene glycol 400, and stirred at 62°C for 39 minutes; the mixed solution is then cooled to 8°C, and then 3.8 parts of 0.2wt.% copper peptide aqueous solution are added thereto, and the mixed solution is stirred in a high-speed homogenizer at 8600 rpm for 8 minutes; the mixed solution is then subjected to high-pressure treatment at a pressure of 1000 bar for 13 minutes, and finally the complex solution is placed in a freeze dryer and dried for 22 hours to obtain the copper-peptide nanolipid complex.
[0076] A method for preparing a composite anti-aging and skin-tightening polypeptide skin care product of this embodiment comprises the following steps: S1. Prepare the aqueous phase: add 60% of the total weight of deionized water into a stirring container, stir at room temperature at a stirring rate of 420 rpm, add carbomer, xanthan gum, disodium EDTA, sodium ascorbyl phosphate and triethanolamine in sequence, stir for 36 minutes until all components are completely dissolved to form a uniform and transparent aqueous phase solution, and then.
[0077] S2. Prepare the oil phase: Add squalane, caprylic / capric triglyceride, cholesterol, phospholipids, ceramide and polysorbate-60 into another container, slowly heat to 62°C, and stir at a stirring rate of 320 rpm for 26 minutes until the components are completely mixed to form a uniform oil phase solution.
[0078] S3. Preparation of active ingredients: Prepare nanoparticle suspension, polypeptide active solution, moisturizing solution and antioxidant solution respectively. The preparation method of nanoparticle suspension is as follows: disperse the loaded acetyl octapeptide-3 nanoparticles in 10% of the total mass of deionized water, stir at a stirring rate of 160 rpm for 16 minutes, until a uniform nanoparticle suspension is formed. The preparation method of polypeptide active solution is as follows: dissolve the copper peptide nanolipid complex and palmitoyl pentapeptide-4 in 10% of the total mass of deionized water, stir at a stirring rate of 210 rpm for 13 minutes, until completely dissolved, to form a polypeptide active solution. The preparation method of moisturizing solution is as follows: dissolve sodium hyaluronate, glycerol, butylene glycol, propylene glycol and panthenol in 20% of the total mass of deionized water, stir at a stirring rate of 260 rpm for 18 minutes, and form a uniform moisturizing solution. The preparation method of the antioxidant solution is as follows: vitamin E, coenzyme Q10 and resveratrol are dissolved in an appropriate amount of an oil phase solvent, and stirred at a stirring rate of 310 rpm for 13 minutes until they are fully dissolved to form a uniform antioxidant solution.
[0079] S4. Emulsification process: The oil phase prepared in step S2 is slowly added to the water phase in step S1, and emulsified in a high-speed emulsifier at an emulsification rate of 5600 rpm, and the temperature is maintained at 62° C. The emulsification time is 26 min until a stable emulsion is formed.
[0080] S5. Prepare the finished product: slowly add the nanoparticle suspension, polypeptide active solution, moisturizing solution, antioxidant solution and citric acid-sodium citrate buffer prepared in step S3 to the emulsion in sequence, and control the addition speed to be 12 mL / min. After the addition is completed, stir at a stirring rate of 420 rpm for 39 minutes at a temperature of 46°C; after the stirring is completed, naturally cool the emulsion to room temperature, slowly add phenoxyethanol, ethylhexylglycerin and seaweed extract, and continue to stir at a stirring rate of 210 rpm for 13 minutes to mix evenly; then place the emulsion in a vacuum degassing machine, and degas under a vacuum condition of -0.09 MPa for 13 minutes to remove residual bubbles in the emulsion. After the degassing is completed, the emulsion is placed in a clean container and sealed for storage to finally obtain a compound anti-aging and firming polypeptide skin care product.
[0081] Comparative Example 1 The method is basically the same as Example 1, except that the surface of the glutamine-based nanoparticles is not loaded with acetyl octapeptide-3.
[0082] Comparative Example 2 The method is basically the same as Example 1, except that an equal amount of copper peptide is used to replace the copper peptide nanolipid complex, so the copper peptide is not encapsulated in the liposome.
[0083] Comparative Example 3 The method is basically the same as Example 1, except that the loaded acetyl octapeptide-3 nanoparticles are not added into the skin care product.
[0084] Comparative Example 4 The method is basically the same as Example 1, except that the copper peptide nanolipid complex is not added to the skin care product.
[0085] Comparative Example 5 The method is basically the same as Example 1, except that xanthan gum and carbomer are not added to the skin care product.
[0086] Comparative Example 6 The method is basically the same as Example 1, except that 0.30 parts of citric acid-sodium citrate buffer solution is added to the skin care product, and the pH value of the skin care product is 4.2.
[0087] Performance Testing: The determination of antioxidant activity includes the test of three free radical scavenging abilities. First, the antioxidant capacity of the sample is evaluated by measuring the scavenging rate of the DPPH• free radical. DPPH• is a highly chemically active free radical with a single electron. Its alcohol solution has a characteristic absorption peak at 517 nm and is dark purple. The experiment mixed samples of different concentrations with DPPH• solution, reacted at 25°C in the dark for 1 hour, measured the absorbance change, and calculated the scavenging rate. The scavenging rate reflects the sample's ability to scavenge DPPH• free radicals. Secondly, the pyrogallol method was used to determine the sample's ability to scavenge superoxide anion free radicals (O 2 - ) clearance rate. In the experiment, samples of different concentrations were mixed with Tris-HCl buffer solution, reacted in a 25°C water bath for 30 minutes, and then pyrogallol solution was added to measure the change of absorbance at 320 nm over time, calculate the oxidation rate, and compare the oxidation rate of the buffer solution to obtain the superoxide anion clearance rate of the sample. This method reflects the sample's ability to scavenge oxygen free radical precursors. Finally, Fe² + / H 2 O 2 The system measures the scavenging rate of the sample for hydroxyl radicals (•OH). Hydroxyl radicals can convert o-phenanthroline-Fe² + Oxidized to phenanthroline -Fe³ + , which reduces the absorbance at 536 nm. 4 , H 2 O 2 After mixing the reagents, react at 37°C for 60 minutes, measure the absorbance of different systems, and calculate the hydroxyl radical scavenging rate. This method is used to evaluate the sample's ability to scavenge •OH and its antioxidant properties.
[0088] In order to evaluate the long-term release ability of the compound anti-aging firming peptide skin care product, the following experimental scheme can be designed. By simulating the skin environment, combining in vitro release experiments and multi-time point detection, the release behavior and sustained release ability of active ingredients in skin care products are systematically tested. The experiment adopts the dialysis bag diffusion method, and the skin care product samples are loaded into a dialysis bag with a molecular weight cutoff of 10 kDa to simulate the selective permeability characteristics of the skin barrier. The dialysis bag is placed in a receiving solution containing 37℃ Tris-HCl buffer (pH 5.5), which simulates the acidic environment and body temperature conditions of the skin, and maintains a constant stirring rate (100rpm) to prevent the limitation of the diffusion boundary layer. 1 mL of the receiving solution is sampled every 2 hours (and an equal amount of fresh buffer is supplemented at the same time), and the sampling is continued for 48 hours. The concentrations of key active ingredients such as acetyl octapeptide-3, copper peptide and palmitoyl pentapeptide-4 in the samples are determined by high performance liquid chromatography (HPLC), and the release curves are drawn. The cumulative release amount (the total amount released per unit time as a percentage of the initial load) reflects the release rate and release sustainability of the active ingredients. At the same time, the time required for the cumulative release to exceed 80% (T80%) and the release stability are used as evaluation indicators, and the release curve is fitted with a zero-order, first-order or Higuchi model to evaluate the release mechanism. Finally, by comparing the release characteristics of different active ingredients, the performance advantages of skin care products in long-term release are verified.
[0089] The penetration ability test was conducted using in vitro transdermal experiments and fluorescent labeling technology. Through the Franz diffusion cell experiment, the skin care product samples were applied to the donor chamber, and the receiving chamber was filled with a buffer solution that simulated the skin environment (such as PBS buffer at 37°C). Samples were taken at different time points, and the concentrations of key active ingredients (such as acetyl octapeptide-3 and copper peptide) in the buffer solution were detected using HPLC. The transdermal curve was drawn to evaluate the release and penetration efficiency of the active ingredients. At the same time, by fluorescently labeling the active ingredients and combining confocal microscopy (CLSM) to observe the distribution of active ingredients in the skin cross-section, the ability of the active ingredients to penetrate the stratum corneum and reach the dermis can be intuitively demonstrated. This experiment can verify whether the nanocarriers of skin care products effectively promote the transdermal absorption of active ingredients and act on the deep layers of the skin.
[0090] Anti-aging performance testing can be performed through in vitro cell experiments. In the human dermal fibroblast (HDF) model, skin care product samples are added to treat cells at different concentrations for 48 hours, and then the expression levels of collagen I, III and elastin are detected by Western Blot or ELISA to evaluate the promotion of active ingredients on the production of skin structural proteins.
[0091] The properties of the coatings of Examples 1 to 7 and Comparative Examples 1 to 4 are summarized in Table 2.
[0092] Table 2 Performance summary of the skin care products of Examples 1 to 4 and Comparative Examples 1 to 6
[0093] The main difference between Comparative Example 1 and Example 1 is that the surface of the glutamine-based nanoparticles is not loaded with acetyl octapeptide-3. As can be seen from Table 2, Comparative Example 1 has a lower antioxidant performance (DPPH·, O 2 - , OH free radical scavenging rate) and anti-aging performance (collagen I, III and elastin expression) are significantly lower than those in Example 1, and the transdermal rate and T80% also show a significant decrease. This is because acetyl octapeptide-3 is an effective antioxidant and anti-aging ingredient that can directly scavenge free radicals and promote the expression of collagen and elastin. At the same time, its loading on the surface of nanoparticles can significantly improve stability and transdermal absorption efficiency. Therefore, Comparative Example 1 shows a significant disadvantage in many performances.
[0094] The main difference between Comparative Example 2 and Example 1 is that the copper peptide is not encapsulated in liposomes, but exists in a free state. As can be seen from Table 2, the antioxidant performance of Comparative Example 2 is slightly lower than that of Example 1, especially in terms of OH clearance rate and anti-aging performance (such as the improvement of collagen I, III and elastin), while the transdermal rate and T80% also slightly decreased. This is because when the copper peptide exists in a free state, its stability and permeability are low and it is easily affected by the skin surface environment, while the encapsulation of liposomes can protect the copper peptide from degradation, improve its transdermal absorption efficiency, and thus enhance the antioxidant and anti-aging effects.
[0095] The main difference between Comparative Example 3 and Example 1 is that nanoparticles loaded with acetyl octapeptide-3 are not added to the skin care product. As can be seen from Table 2, the antioxidant and anti-aging properties of Comparative Example 3 are significantly lower than those of Example 1, especially the OH clearance rate and collagen enhancement ability are significantly reduced, while T80% and transdermal rate are also reduced. This is because acetyl octapeptide-3, as an important antioxidant and anti-aging ingredient, can not only directly remove free radicals, but also promote the production of collagen and elastin by regulating fibroblast function, and the loading of nanoparticles can improve its stability and permeability. The lack of this ingredient has a significant impact on the overall performance of Comparative Example 3.
[0096] The main difference between Comparative Example 4 and Example 1 is that no copper peptide nanolipid complex is added to the skin care product. As can be seen from Table 2, the antioxidant performance of Comparative Example 4 is slightly lower than that of Example 1, especially the •OH clearance rate is poor, and the anti-aging performance and transdermal rate are also slightly reduced. This is because copper peptide is an important antioxidant and anti-aging ingredient, and its nanolipid complex form can significantly improve the skin absorption rate and stability, while the unencapsulated copper peptide is relatively weak in transdermal penetration and antioxidant activity, so Comparative Example 4 is inferior in many performances.
[0097] The main difference between Comparative Example 5 and Example 1 is that xanthan gum and carbomer are not added to the skin care product. As can be seen from Table 2, the antioxidant performance of Comparative Example 5 is close to that of Example 1, but it is slightly lower than Example 1 in terms of long-term release capacity (T80%) and transdermal rate, and the performance of anti-aging performance is also slightly reduced. This is because xanthan gum and carbomer, as thickeners and stabilizers, can improve the stability and adhesion of the ingredients of skin care products, prolong the action time of active ingredients on the skin surface, thereby enhancing the long-term release and anti-aging effects. Therefore, Comparative Example 5 without adding these ingredients is slightly insufficient in these aspects.
[0098] The main difference between Comparative Example 6 and Example 1 is that citric acid-sodium citrate buffer is added to the skin care product and the pH is adjusted to 4.2. As can be seen from Table 2, the antioxidant performance of Comparative Example 6 is close to that of Example 1, but it is slightly lower than Example 1 in terms of long-term release capacity (T80%) and transdermal rate, and the anti-aging performance is also slightly inferior. This is because although the pH value of 4.2 is closer to the natural acidic environment of the skin and helps to improve the stability of some active ingredients, the citric acid-sodium citrate buffer may have a certain effect on the structure and component release behavior of some nanocarriers, resulting in a slight decrease in long-term release and anti-aging effects.
[0099] In summary, the performance comparison between Examples 1 to 4 and Comparative Examples 1 to 6 shows that the selection of key active ingredients, loading form and the role of additives in compound skin care products have a significant impact on the comprehensive performance of the product. Example 1 exhibits a relatively balanced performance, while Example 3 performs best in antioxidant performance, long-lasting release capacity, transdermal absorption and anti-aging performance, fully verifying the synergistic effect of acetyl octapeptide-3 and copper peptide nanolipid complex loading form. In contrast, the performance of the comparative example is greatly affected by the lack of key ingredients or additives, especially in antioxidant and anti-aging, showing significant disadvantages. Specifically, Comparative Examples 1 and 3 lacked acetyl octapeptide-3 and its loaded form, resulting in a significant decrease in antioxidant capacity and anti-aging performance; Comparative Examples 2 and 4 showed lower transdermal absorption efficiency and free radical scavenging ability due to the lack of copper peptide encapsulation or lack thereof; although Comparative Example 5 had an antioxidant performance close to that of Example 1, due to the lack of xanthan gum and carbomer, the long-term release and anti-aging effects were weakened; although Comparative Example 6 improved some performance by adjusting the pH value, it was still slightly inferior to Example 1 in terms of long-term release and transdermal absorption.
[0100] In general, the excellent performance of the examples is due to the scientific ratio of active ingredients, advanced nano-carrier technology and the rational use of excipients. These factors work together to significantly enhance the antioxidant, long-lasting release, transdermal absorption and anti-aging effects of skin care products. The comparative study further verifies the irreplaceable role of key ingredients and formula design in the overall performance of the product, providing an important basis for the optimized formula design of skin care products.
[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.
Claims
1. A compound anti-aging and firming polypeptide skin care product, characterized in that: The invention comprises the following components in weight fractions: 2.0-5.0 parts of loaded acetyl octapeptide-3 nanoparticles, 1.0-2.0 parts of copper peptide nanolipid complex, 1.0-3.0 parts of palmitoyl pentapeptide-4, 0.5-1.5 parts of sodium hyaluronate, 3.0-5.0 parts of glycerol, 2.0-4.0 parts of butylene glycol, 2.0-4.0 parts of squalane, 1.0-3.0 parts of caprylic / capric triglyceride, 1.5-3.0 parts of polysorbate-60, 0.2-0.4 parts of carbomer, 0.1-0.3 parts of xanthan gum, 0.2-0.3 parts of triethanolamine, 0.5-1.0 parts of vitamin E, 0.5-1.0 parts of panthenol, 0.5-1.0 parts of seaweed extract, 0.6-0.8 parts of phenoxyethanol, 0.5-1.0 parts of ethylhexylglycerol, and coenzyme Q10. 0.5-1.0 parts, resveratrol 0.5-0.8 parts, ceramide 0.5-1.0 parts, cholesterol 0.2-0.5 parts, phospholipids 1.0-2.0 parts, disodium EDTA 0.1-0.3 parts, sodium ascorbyl phosphate 0.1-0.2 parts, propylene glycol 1.0-2.0 parts, deionized water 60.0-65.0 parts, citric acid-sodium citrate buffer 0.05-0.1 parts; The acetyl octapeptide-3 loaded nanoparticles are composed of glutamine-based nanoparticles and acetyl octapeptide-3 loaded on the glutamine-based nanoparticles; The glutamine-based nanoparticles are prepared by copolymerization of hydroxyethyl methacrylate and N-methacryloyl-(L)-glutamic acid through emulsion polymerization. The N-methacryloyl-(L)-glutamic acid is obtained by chlorination reaction of L-glutamic acid-5-methyl ester and methacryloyl chloride; The copper-peptide-lipid nanocomposite liposome is prepared from copper peptide and nanoliposome by emulsification combined with high-pressure homogenization technology; The pH of the polypeptide skin care product is 4.5-5.
5.
2. A compound anti-aging and skin-tightening polypeptide skin care product according to claim 1, characterized in that: The preparation method of the acetyl octapeptide-3 loaded nanoparticles is as follows: by weight, 2.0-5.0 parts of glutamine-based nanoparticles and 0.01-0.03 parts of sodium chloride are added to 30-40 parts of 0.4 mg / mL acetyl octapeptide-3 solution, the mixture is placed in a beaker, the stirring rate is 30-40 rpm, the stirring time is 20-40 min, the pH of the solution is adjusted to 3.4-6.0 with a citric acid buffer during the stirring process, after the stirring is completed, the obtained nanoparticle suspension is transferred to a centrifuge, centrifuged at a speed of 10000-12000 rpm for 20-25 min, the supernatant is discarded, the nanoparticle precipitate is separated, the obtained precipitate is washed 3 times with deionized water, the amount used for each washing is twice the volume of the suspension, after the washing is completed, the washed nanoparticle suspension is liquid nitrogen frozen and placed in a freeze dryer for 20-24 h, and finally the acetyl octapeptide-3 loaded nanoparticles are obtained.
3. A compound anti-aging and skin-tightening polypeptide skin care product according to claim 1 or 2, characterized in that: The preparation method of the glutamine-based nanoparticles is as follows: in parts by weight, deionized water is used as a solvent, 270.0-280.0 parts of polyvinyl alcohol are dissolved in 20.0-30.0 parts of deionized water, the mixture is placed in a beaker, the stirring rate is set to 300-350 rpm, the stirring time is 30-40 minutes, until a uniform mixed solution is formed, then 0.50-0.65 parts of hydroxyethyl methacrylate, 0.80-1.1 parts of N-methacryloyl-(L)-glutamic acid and 0.29-0.31 parts of ethylene glycol dimethacrylate crosslinking agent are sequentially added to the mixed solution, the stirring rate is 300-350 rpm, and the stirring is continued for 20-30 minutes until a uniform reaction solution is formed, 18.0-20.0 parts of 50 wt.% potassium persulfate solution are slowly added dropwise to the reaction solution, and the flow rate is 10.0-12.0 Nitrogen was purged at sccm for 240-360 s to remove oxygen from the solution. The mixed solution was heated to 60-70°C at a heating rate of 2°C / min and stirred at a stirring rate of 120-150 rpm for 240-300 min under the heating condition until the reaction was complete and an emulsion mixture was formed. After the reaction was completed, the mixture was naturally cooled to room temperature. The cooled emulsion was transferred to a centrifuge and centrifuged at a centrifugal rate of 11000-12000 rpm for 20-25 min. The precipitate was separated and the supernatant was discarded. The obtained precipitate was washed alternately with anhydrous ethanol and deionized water for 3-5 times, each time with an amount twice that of the precipitate, to remove unreacted monomers and impurities. After washing, the precipitate was placed in a vacuum drying oven and dried at room temperature for 16-20 h to finally obtain glutamine-based nanoparticles.
4. A compound anti-aging and skin-tightening polypeptide skin care product according to claim 1 or 3, characterized in that: The preparation method of N-methacryloyl-(L)-glutamic acid is as follows: by weight, 4.0-6.0 parts of L-glutamic acid-5-methyl ester and 0.10-0.25 parts of hydroquinone are dissolved in 100 parts of dichloromethane, mixed evenly and the solution is cooled to -5-0°C, then 10-15 parts of triethylamine are added to the solution, 3.0-5.0 parts of methacryloyl chloride are slowly poured into the solution under a nitrogen atmosphere, the solution is magnetically stirred at room temperature for 90-120 minutes, and after the reaction is completed, unreacted methacryloyl chloride is extracted with 10 wt.% NaOH, and then the extracted solution is evaporated in a rotary evaporator for 10-14 hours to finally obtain N-methacryloyl-(L)-glutamic acid.
5. The compound anti-aging and skin-tightening polypeptide skin care product according to claim 1, characterized in that: The preparation method of the copper-peptide nanolipid complex is as follows: 5.0-10.0 parts of soybean lecithin and 5.0-10.0 parts of cholesterol are added to 200 parts of polyethylene glycol 400, and stirred at 50-70°C for 30-45 minutes; then the mixed solution is cooled to 5-10°C, and then 2.0-5.0 parts of 0.2wt.% copper peptide aqueous solution are added thereto, and the mixed solution is stirred in a high-speed homogenizer at 8000-9000 rpm for 5.0-10 minutes; then the mixed solution is subjected to high-pressure treatment at a pressure of 1000 bar for 10-15 minutes, and finally the complex solution is placed in a freeze dryer and dried for 20-24 hours to obtain the copper-peptide nanolipid complex.
6. A method for preparing a composite anti-aging and skin-tightening polypeptide skin care product according to any one of claims 1 to 5, comprising the following steps: S1. Prepare the aqueous phase: add 60% of the total weight of deionized water into a stirring container, stir at room temperature at a stirring rate of 300-500 rpm, add carbomer, xanthan gum, disodium EDTA, sodium ascorbyl phosphate and triethanolamine in sequence, and stir for 30-40 min until all components are completely dissolved to form a uniform and transparent aqueous solution; S2. Prepare the oil phase: add squalane, caprylic / capric triglyceride, cholesterol, phospholipids, ceramide and polysorbate-60 into another container, slowly heat to 50-70°C, and stir at a stirring rate of 200-400 rpm for 20-30 min until the components are completely mixed to form a uniform oil phase solution; S3. Preparing active ingredients: preparing nanoparticle suspension, polypeptide active solution, moisturizing solution and antioxidant solution respectively; S4. Emulsification process: the oil phase prepared in step S2 is slowly added to the aqueous phase in step S1, and emulsified at an emulsification rate of 5000 to 6000 rpm in a high-speed emulsifier, and the temperature is maintained at 50 to 70 ° C, and the emulsification time is 20 to 30 min until a stable emulsion is formed; S5. Prepare the finished product: slowly add the nanoparticle suspension, polypeptide active solution, moisturizing solution, antioxidant solution and citric acid-sodium citrate buffer prepared in step S3 to the emulsion in sequence, and control the addition speed to be 12 mL / min. After the addition is completed, stir at a stirring rate of 300-500 rpm for 30-45 minutes in the range of 40-50°C; after the stirring is completed, the emulsion is naturally cooled to room temperature, and phenoxyethanol, ethylhexylglycerin and seaweed extract are slowly added, and the stirring is continued at a stirring rate of 150-250 rpm for 10-15 minutes to mix evenly; then the emulsion is placed in a vacuum degassing machine, and degassed under a vacuum condition of -0.08~-0.1 MPa for 10~15 minutes to remove residual bubbles in the emulsion. After the degassing is completed, the emulsion is placed in a clean container and sealed for storage to finally obtain a compound anti-aging and firming polypeptide skin care product.
7. The method for preparing a composite anti-aging and skin-tightening polypeptide skin care product according to claim 6, characterized in that: The preparation method of the nanoparticle suspension in step S3 is: dispersing the loaded acetyl octapeptide-3 nanoparticles in 10% of the total mass of deionized water, stirring at a stirring rate of 100-200 rpm for 10-20 minutes until a uniform nanoparticle suspension is formed.
8. The method for preparing a composite anti-aging and firming polypeptide skin care product according to claim 6, wherein the method for preparing the polypeptide active solution in step S3 is: dissolving the copper peptide nanolipid complex and palmitoyl pentapeptide-4 in 10% of the total mass of deionized water, stirring at a stirring rate of 150-250 rpm for 10-15 minutes until completely dissolved to form a polypeptide active solution.
9. The method for preparing a composite anti-aging and firming polypeptide skin care product according to claim 6, wherein the method for preparing the moisturizing solution in step S3 is: dissolving sodium hyaluronate, glycerin, butylene glycol, propylene glycol and panthenol in 20% of the total mass of deionized water, respectively, and stirring at a stirring rate of 200-300 rpm for 15-20 minutes to form a uniform moisturizing solution.
10. The method for preparing a composite anti-aging and firming polypeptide skin care product according to claim 6, wherein the method for preparing the antioxidant solution in step S3 is: dissolving vitamin E, coenzyme Q10 and resveratrol in an appropriate amount of an oil phase solvent, stirring at a stirring rate of 250-350 rpm for 10-15 minutes until fully dissolved to form a uniform antioxidant solution.
Citation Information
Patent Citations
Polypeptide cosmetic skincare product
CN107822973A
Polypeptide protein-based silicone modified skin care product and preparation method thereof
CN108938453A
Cited By
Composition for skin repair and anti-aging and preparation method thereof
CN121059467A